Transformasi Nilai Qawlan Layyinan dalam Relasi Keluarga Modern di Kecamatan Darussalam - Fitri Meliya Sari; Muhammad Rijaalul Ikram (Sadida Islamic Communications and Media Studies, 2025)
This study aims to analyze the application of Qawlan Layyinan values in fostering harmonious family relationships within modern households in Darussalam District, Aceh Besar. Qawlan Layyinan, meaning gentle and kind speech, represents an Islamic communication principle that sustains family harmony amidst the challenges of modernization. This research employs a qualitative descriptive approach through in-depth interviews, observations, and documentation involving several Muslim families. The findings reveal that soft, empathetic, and compassionate communication plays a crucial role in resolving conflicts and strengthening emotional bonds among family members. The value of Qawlan Layyinan not only reflects ethical speech but also functions as a spiritual strategy for achieving a sakinah, mawaddah, wa rahmah family. Its implementation is consistent with Relational Communication Theory and serves as a moral solution to communication crises in modern families.